Effects of salinity on embryonic development of Cryphiops caementarius (Crustacea: Palaemonidae) incubated in vitro - Fuentes, Adelhi S. (2010)
The aim of this work was to study the effects of salinity on the development of embryos of Cryphiops caemen- tarius incubated in vitro. We used embryos of early development, from a unique female. The incubators were of 400 mL, with 4 salinity treatments of 0, 10, 20 and 30 ‰, three replicates, and 200 embryos each incubator. The 80% of the water was renewed frequently. The salinities between 0‰ and 30‰ did not affect the develop- ment of the embryos up to the stage 6. The salinities of 10 and 20 ‰ caused delay of the development of the stages 7 and 8; and the salinity of 30‰ caused death of the stage 7. In freshwater the 70,3% of the embryos survived and larvae were normal; on the other hand in salinity at 10‰ to 13,5% and 20‰ only 7,9% achieved larvae hatch but with deformations.